Prospective Trial of Water Vapor Thermal Therapy for Treatment of Lower Urinary Tract Symptoms Due to Benign Prostatic Hyperplasia in Subjects with a Large Prostate: 6- and 12-month Outcomes - Woo, Henry; Levin, Richard; Cantrill, Christopher; Zhou, Shaw; Neff, Donald; Sutton, Mark; Bailen, James; Darson, Michael; Horgan, John; Zantek, Paul; Marty-Roix, Robyn (European urology open science (Online), 2023)
Rezūm water vapor therapy is a safe and effective option for men with a large prostate (80–150 cm3) who desire minimally invasive treatment for their benign prostatic obstruction. Current guidelines recommend Rezūm water vapor thermal therapy for the treatment of benign prostatic hyperplasia (BPH) for prostate glands ranging in volume from 30 to 80 cm3. Few prospective studies have specifically evaluated the use of Rezūm for larger prostates. To evaluate the safety and efficacy of water vapor thermal therapy in patients with a prostate gland >80 cm3 and ≤150 cm3. In this prospective, single-arm study at seven centers in the USA, subjects were males aged >50 yr with symptomatic BPH and prostate volume of >80 cm3 and ≤150 cm3. Rezūm was used to deliver sterile water vapor via a transurethral approach to ablate targeted areas of prostate tissue. The primary efficacy outcome was response to therapy, defined on a per-patient basis as a ≥30% improvement in International Prostate Symptom Score (IPSS) from baseline to 6 mo. The primary safety outcome was a composite of serious device-related safety events. Secondary outcomes included catheterization for device-related retention. IPSS outcomes over time were analyzed via generalized estimating equations. Among 47 eligible patients, prostate volume ranged from 80.8 to 148.1 cm3. All patients completed 6-mo follow-up, and 40/47completed 12-mo follow-up. At 6 mo, 83% were treatment responders according to the primary efficacy endpoint. The mean IPSS improvement at 6 mo was 11.9 ± 7.5 points, reflecting significant improvement. The primary safety outcome was met, with no occurrence of device-related composite safety events. The study is limited by the nonrandomized design and early termination, unrelated to safety or effectiveness. Our results are consistent with previous findings for prostate glands of up to 80 cm3, and indicate the safety and efficacy of Rezūm for BPH in patients with a larger prostate. Rezūm therapy, in which water vapor is used to treat targeted areas of the prostate, is currently recommended for patients with benign enlargement of the prostate and a prostate size of up to 80 cm3. We found that this treatment was also effective and safe in patients with a larger prostate of 80–150 cm3.